2015
DOI: 10.1186/s12993-015-0086-4
|View full text |Cite
|
Sign up to set email alerts
|

Long-term influence of recurrent acute otitis media on neural involuntary attention switching in 2-year-old children

Abstract: BackgroundA large group of young children are exposed to repetitive middle ear infections but the effects of the fluctuating hearing sensations on immature central auditory system are not fully understood. The present study investigated the consequences of early childhood recurrent acute otitis media (RAOM) on involuntary auditory attention switching.MethodsBy utilizing auditory event-related potentials, neural mechanisms of involuntary attention were studied in 22–26 month-old children (N = 18) who had had an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
22
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(23 citation statements)
references
References 47 publications
1
22
0
Order By: Relevance
“…Some evidence shows that the expression of Bcl-2 was suppressed in VPA-induced ASD rats 26. BDNF plays an important role in survival and differentiation of nervous system, and BDNF is involved in the pathogenesis of a wide range of psychiatric disorders 27. The levels of BDNF and Bcl-2 were decreased in ASD patients 28,29.…”
Section: Discussionmentioning
confidence: 99%
“…Some evidence shows that the expression of Bcl-2 was suppressed in VPA-induced ASD rats 26. BDNF plays an important role in survival and differentiation of nervous system, and BDNF is involved in the pathogenesis of a wide range of psychiatric disorders 27. The levels of BDNF and Bcl-2 were decreased in ASD patients 28,29.…”
Section: Discussionmentioning
confidence: 99%
“…One hypothesis that explains the persistence of these behavioral deficits when occurring during childhood is that HL during a developmental critical period induces persistent changes to inhibitory synapse function that degrade central auditory processing (Sanes, 2013). Indeed, transient childhood HL is associated with altered central auditory physiology, both in the brainstem and cortex (Folsom et al, 1983;Gunnarson and Finitzo, 1991;Hall and Grose, 1993;Haapala et al, 2014Haapala et al, , 2016. Here, we ask whether developmental HL-induced auditory behavioral deficits can be rescued by maintaining or restoring normal inhibitory synaptic function.…”
Section: Introductionmentioning
confidence: 99%
“…Do et al [4] discovered that functional coupling between striatal and cortical regions is associated with increased craving in adolescent smokers. Sutherland et al [5] observed that smoking is associated with convergent structural decreases in the left insula, right cerebellum, parahippocampus, multiple prefrontal cortex regions, and the thalamus. Mcclernon et al [6] provided evidence that abstinence-induced deficits in working memory and changes in the underlying brain function are mostly due to abstinence from nicotine rather than non-nicotine factors.…”
Section: Introductionmentioning
confidence: 99%